Pathways to accessing healthcare and associated factors among young febrile children admitted to the pediatric wards of Teaching Hospital Jaffna - Rishad, M.H.M.; Faseeha, S.F.; Aathil Ahamed, Y.; Wijayabandara, S.G.M.U.S.; Mhathulaa, K.; Kumar, R.; Umasankar, N. (University of Jaffna, 2024)
Background and objective: Fever is a common reason for seeking healthcare for young children; delays could lead to adverse health outcomes. This study describes the pathways and time taken to access healthcare among young children admitted with fever to the paediatric wards of Teaching Hospital Jaffna (THJ). Methods: This was a hospital-based descriptive cross-sectional study carried out among caregivers of young children (<5 years) in the paediatric wards of THJ. Consecutive sampling was used until sample size was achieved. Data were collected at the bedside with an interviewer-administered questionnaire with responses entered directly into the KoboCollect tool. Data were analyzed with SPSS (v20). Chi-square test was used to test for associations (critical level 0.05). Results: In total, 436 caregivers participated (response rate 100%). Majority were 18-35 years (62.8%), mothers (93.6%) with at least O/L qualifications (78.2%). Most children were >1 year (84%) and male (54.4%). In total, 86.2% of children were self-medicated, 48.9% saw a general practitioner (GP) or other primary care provider, 21.1% consulted a private specialist, and 30% did not seek any healthcare prior to admission. Age of the child and type of provider accessed were associated with self-medication; older children and those seen by a general practitioner or other primary care provider were more likely to be self-medicated (p≤0.05). Marital status, education level and a family member in the health sector were associated with consulting a specialist; married caregivers, a higher education level and those with a family member employed in the health sector were more likely to consult a specialist (p≤0.05). With respect to time taken, 50.9% saw a healthcare provider within 24 hours. Age of the child and education level of the caregiver were associated with time taken to access care; caregivers seeking care for an infant with higher education level were more likely to seek care within 24 hours (p≤0.05). Conclusion and recommendation: Many children with fever were self-medicated and not seen by a general practitioner or other primary healthcare provider before admission to THJ. Only half accessed health care within 24 hours of fever onset. Health authorities should raise public awareness on the importance and advantages of accessing primary care and investigate the safety of self-medication practices.
Keywords: Healthcare access; Primary care provider; Fever; Young children; Jaffna